Understanding learner engagement on a blended course including a MOOC - Sarah Cornelius; Colin Calder; Peter Mtika (Association for Learning Technology, 2019)
The use of Massive Open Online Courses (MOOCs) in blended learning contexts is becoming increasingly common, but relatively little is known about the experiences of on-campus learners taking MOOCs. This article reports research that explored the experiences of on-campus learners taking a blended course which included a MOOC. Use of the UK Engagement Survey provided a focus on engagement and permitted comparisons with a wider cohort of on-campus learners. Findings show that there were no differences between learners on the blended course and the wider cohort of on-campus learners for some aspects of engagement. However, learners on the blended course were more engaged than on-campus learners on specific aspects measured by the UKES survey including those which appear related to social learning. Evidence from a small number of interviews is used to explore issues raised, and informed by the Community of Inquiry framework, factors which influence blended learners' engagement with the MOOC are discussed. Some of the findings support the call for amendments to the community of inquiry framework for MOOC contexts and provide evidence of issues related to social and teaching presence that may need additional consideration.